Identification of the sacrococcygeal epidural space using the nerve stimulation test or the running-drip method in dogs. (May 2020) - Martinez-Taboada, Fernando; Otero, Pablo E.; Laredo, Francisco; Belda, Eliseo
Abstract: Objective: To compare the nerve stimulation test (group NS) with the running-drip method (group RUN) for successful identification of the sacrococcygeal (SCo) epidural space prior to drug administration in dogs. Animals: A total of 62 dogs. Study design: A randomized clinical study. Methods: Dogs requiring an epidural anaesthetic as part of the multimodal anaesthetic plan were randomly allocated to one of the two study groups. In group NS, the epidural space was located using an insulated needle connected to a nerve stimulator; in group RUN, the epidural space was identified using a Tuohy needle connected to a fluid bag elevated 60 cm above the spine via an administration set. The success of the technique was assessed 5 minutes after epidural injection by the disappearance of the patella reflex. Data were checked for normality, nonparametric data was analysed using a Mann–Whitney U test and success rate was analysed using a Fisher's exact test. The significance level was set at p < 0.05, and the results are presented in absolute values, percentage (95% confident interval) and median (range). Results: The success in identification of the epidural space did not differ between groups NS and RUN [87.1% (70.2%–96.4%) versus 90.3% (74.2%–98%); p  = 1.000]. The time required for identification of the epidural space was shorter in group RUN [26 (15–53) seconds] than in group NS [40 (19–137) seconds] ( p  = 0.0225). No other differences were found in any studied variables. Conclusion: and clinical relevance In this study, both RUN and NS techniques were successful in identifying the epidural space at the SCo intervertebral space. RUN requires no specialised equipment, can be performed rapidly and offers an alternative to the NS for use in general veterinary practice.